2015
DOI: 10.3139/146.111146
|View full text |Cite
|
Sign up to set email alerts
|

Joining steel to aluminum alloy by resistance spot welding with a rivet

Abstract: Joining steel to aluminum alloy by resistance spot welding with a rivet A new joining method, termed resistance spot welding with a rivet, was tried to weld steel to aluminum alloy. Scanning electron microscopy studies of the interfacial microstructures revealed the presence of an FeAl reaction layer at the rivet/aluminum alloy interface, and of FeAl 3 at the steel/ aluminum alloy interface. A tensile shear load of a maximum of 3.85 kN was obtained at a welding current of 21 kA. The results reveal that resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Although the reaction layer is not the main load-bearing part of the REW joint, the close connection between aluminum and steel may improve the mechanical properties of the joint. 20 The EDS test was used to acquire the weight and atomic percentage of the iron and aluminum (Table 2). According to Ma et al, 30 the Fe-Al IMC phases were determined by the atomic percent of the iron and aluminum, indicating that the IMCs formed by the DP780/5052Al alloy are Fe 2 Al 5 and FeAl 3 , and the IMC formed by the Q235 rivet/5052Al alloy is FeAl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reaction layer is not the main load-bearing part of the REW joint, the close connection between aluminum and steel may improve the mechanical properties of the joint. 20 The EDS test was used to acquire the weight and atomic percentage of the iron and aluminum (Table 2). According to Ma et al, 30 the Fe-Al IMC phases were determined by the atomic percent of the iron and aluminum, indicating that the IMCs formed by the DP780/5052Al alloy are Fe 2 Al 5 and FeAl 3 , and the IMC formed by the Q235 rivet/5052Al alloy is FeAl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Because the bonding area was sufficiently large, the joint obtained by the hybrid joining process exhibited better tensile-shear mechanical properties. An attempt by Qiu et al 20 to join 6061 aluminum alloy to mild steel via REW revealed FeAl IMC layers at the interface between the rivet and aluminum and FeAl 3 IMC layers at the contact interface between the steel plate and aluminum. Holtschke et al 21 joined the thermally sensitive sandwich material with the high-strength steel through a short welding time REW process.…”
Section: Introductionmentioning
confidence: 99%
“…Ranfeng Qiua et al [27] have also shown in their paper that the REW process is a more efficient method for joining mild steel and aluminum alloy 6061 than the conventional RSW procedure. In addition, the authors have shown that between the element and the aluminum form a compound FeAl, while between the steel and aluminum form a compound FeAl 3 .…”
Section: State Of Art In the Field Of Resistance Spot Welding (Rsw) A...mentioning
confidence: 99%
“…Crystals 2022, 12, 258 12 of 14 capacity of the joint but also to significant damage to the electrode and a reduction in its service life. The comparison was made on the basis of welding current, as a parameter that has the greatest impact on the mechanical properties of RSW and REW joints, so REW can achieve reliable joining of the DP steel and aluminum alloy at relatively low welding currents compared to RSW, which are also the conclusions of most previously published studies [25][26][27].…”
Section: Comparison Of Rsw and Rewmentioning
confidence: 99%
“…Fig. 4 shows the schematic diagram of the four Nguyen et al 40) Shah et al 41) Zhang et al 63) Wang et al 70) Liu et al 71) Tungsten inert gas (TIG) welding Borrisutthekul et al 42) Song et al 43) Liu et al 64) Wang et al 72) Resistance spot welding (RSW) Pouranvari et al 44) Qui et al 45) Satonaka et al 46) Winnicki et al 47) Baskoro et al 48) Su et al 49) Ibrahim et al 50) Oikawa et al 51) Sun et al 52) Zhang et al 65) Sun et al 66) Min et al 73) Feng et al 74) Laser welding Torkamany et al 53) Dharmendra et al 54) Chang et al 67) Liu et al 64) Li et al 75) Cold metal transfer (CMT) Jácome et al 55) Kang et al 56) Shang et al 68) Ren et al 76) Friction stir welding (FSW) Watanabe et al 57) Morishige et al 69) Chang et al 67) Czerwinski et al 77) Element welding Meschut et al 58) Qui et al 59) Ling et al 60) Ling et al 61) Meschut et al 58) Absar et al 62) Manladan et al 78) Manladan et al 79)…”
Section: Steel-aluminum Weldingunclassified